Geomorphological and Glaciological Survey of the Minami-Yamato Nunataks and the Kabuto Nunatak, East Antarctica - Kotaro YOKOYAMA (National Institute of Polar Research, 1976)
A group of six nunataks and an isolated nunatak in the south-west of the Yamato Mountains were explored for the first time in December 1973 by the 14th Japanese Antarctic Research Expedition (1973-1974). The former has been named as the Minami-Yamato Nunataks, and the latter as the Kabuto Nunatak. The main group of the Minami-Yamato Nunataks lying NNW-SSE is composed of five nunataks about 30 km SW from the south end of the Yamato Mountains, and one nunatak is located about 7 km E of the main group. The astro-fixed position of the Kurakake Nunatak in the main group determined is 72°00'30"S, 35°13'30"E. The Kabuto Nunatak is about 20km NNW, isolated from the main group. The elevation of the nunataks are 1,968m to 2,282m above sea level and the surface elevation of the ice sheet is about 1,850m to 2,100m. Between the Yamato Mountains and these nunataks, two trains of ice hills run from NW to SE, which presumably coincides with the general direction of the flow of the ice sheet.